Alternative Arterial Reconstruction After Extended Pancreatectomy. Case Report and Some Considerations of Locally Advanced Pancreatic Cancer - Ielpo, Benedetto; Ferri, Valentina; Caruso, Riccardo; Duran, Hipolito; Diaz, Eduardo; Fabra, Isabel; Oliva, Catalina; Olivares, Sergio; Quijano, Yolanda; Vicente, Emilio (JOP. Journal of the Pancreas, 2013)
Context The clinical benefits of distal pancreatectomy with en bloc celiac axis resection for locally advanced pancreatic body cancer remains controversial and, therefore, declared unresectable in most cases. Appleby first described extended distal pancreatectomy with celiac axis resection for locally advanced gastric cancer. Case report We report a case of a 65-year-old female who presented a locally advanced pancreatic carcinoma with infiltration of celiac axis. After radio-chemo neoadjuvant treatment, the patient underwent exploratory laparoscopy and subsequent distal pancreatectomy with en bloc resection of celiac axis. Arterial reconstruction was necessary as hepatic flow was not adequate, determined by intraoperative Doppler ultrasonography. It consisted of end to end anastomosis with prosthetic graft between hepatic artery directly to the aorta, as an atheromatous plaque was at the origin of the celiac axis. The postoperative course was uneventful with a perfect relief of pain. She presents a long term survival of 36 months, very exceptional for this type of disease. Conclusion The particularity of this case is not only the surgical treatment, rarely offered to these patients, but also and especially the subsequent vascular reconstruction. To our knowledge, this is the first report of this type of arterial reconstruction. Besides, we briefly discuss the recent advances in results of extended distal pancreatectomy with arterial resection for locally advanced pancreatic carcinoma. Image: 3D reconstruction with the stump of the celiac axis.